Specyfika opisu „szczęśliwych” posągów na stacji metra Plac Rewolucji w rosyjskich źródłach internetowych - Joppek, Justyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The purpose of this paper is the descriptive analysis of “happy” statues in the Revolution Square underground station in Russian Internet sources. The range of the study embraces article titles, structure of content presentation, information about the genesis of "rubbing" items, personal stories and iconographic aspect. The research material is taken Russian e-commerce industry websites that operate in the tourism, fashion, interior and home design, financial services, as well as travel blogs.